2017
DOI: 10.1016/j.jcpa.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Myxomatous Degeneration of the Canine Mitral Valve: From Gross Changes to Molecular Events

Abstract: Myxomatous mitral valve disease (MMVD) is the single most common acquired heart disease of the dog, but is also of emerging importance in human medicine, with some features of the disease shared between both species. There has been increased understanding of this disease in recent years, with most research aiming to elucidate the cellular and molecular events of disease pathogenesis. For gross and histological changes, much of our understanding is based on historical studies and there has been no comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 79 publications
1
28
0
Order By: Relevance
“…Dysregulation of the extracellular matrix appears to be central to these changes. Valvular interstitial cells, possibly with post‐transcriptional regulation from microsatellite ribonucleic acids, acquire properties of activated myofibroblasts, and activated myofibroblasts increase proteolytic enzymes, including matrix metalloproteinases, which degrade collagen and elastin faster than they can be produced by unactivated valvular interstitial cells …”
Section: Incidence Pathology and Pathogenesis Of Mmvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of the extracellular matrix appears to be central to these changes. Valvular interstitial cells, possibly with post‐transcriptional regulation from microsatellite ribonucleic acids, acquire properties of activated myofibroblasts, and activated myofibroblasts increase proteolytic enzymes, including matrix metalloproteinases, which degrade collagen and elastin faster than they can be produced by unactivated valvular interstitial cells …”
Section: Incidence Pathology and Pathogenesis Of Mmvdmentioning
confidence: 99%
“…Valvular interstitial cells, possibly with posttranscriptional regulation from microsatellite ribonucleic acids, acquire properties of activated myofibroblasts, and activated myofibroblasts increase proteolytic enzymes, including matrix metalloproteinases, which degrade collagen and elastin faster than they can be produced by unactivated valvular interstitial cells. [13][14][15] Endothelial cell changes and subendothelial thickening also occur, [16][17][18] but these changes do not appear to put dogs with MMVD at increased risk for either arterial thromboembolism or infective endocarditis. Mitral valve prolapse is a common finding in dogs with myxomatous valve degeneration and represents a prominent echocardiographic feature of MMVD in some breeds.…”
Section: Incidence Pathology and Pathogenesis Of Mmvdmentioning
confidence: 99%
“…Atrioventricular node cells 22 represent the only functional link between atria and ventricles 27 . They are separated by a layer of connective tissue that does not produce or drive potential action 5 , so an insulator 25 .…”
Section: µmentioning
confidence: 99%
“…The role of Notch in the angiogenesis of AS may be partly due to the induction of AS in the internal hypoxic environment. Studies have shown that HIF-1a can interact with the intracellular segment of Notch1 to increase cellular response to hypoxia when exposed to atherosclerotic cells in hypoxic conditions [26,27]. In addition, the upregulation of endothelial cell surface Dll4 is likely to be directly regulated by HIF-1a and hypoxia responses to the Dll4 promoter [28].…”
Section: Notch Signalling Pathway Enhances As By Promoting Vascular Ementioning
confidence: 99%